The Impact of Remittances On Labor Supply : The Case of Jamaica - Kim, Namsuk 2003 (The World Bank, 2007)
A puzzle in the recently stagnated economy of Jamaica is that high rates of unemployment have persisted even when real wages have been increasing. This paper examines aspects of the labor supply in an effort to understand why high rates of unemployment have existed with increasing real wages. This is a sign of a badly functioning labor market. The cross-sectional analysis suggests that remittances have some impact on labor supply, especially on labor market participation. The pseudo panel data analysis also confirms that remittances have a strong impact on labor participation but not on weekly working hours. Households with remittance income have a higher reservation wage and have reduced the supply of labor by moving out of the labor force